Learning the Law: Trusts in Business and Commerce - Waters, Donovan W.M. (Journal of Malaysian and Comparative Law, 1987)
In the minds of most lawyers whose home is the common law world the trust is associated with the last will and testament of a testator. In other words, it is to be found in an instrument whereby an individual makes personal arrangements for the distribution of his assets among his desired beneficiaries on the occassion of his death. The husband may desire his widow to have the income of his assets during her lifetime, and that the capital of those assets be distributed among his children when she dies. Here successive interests are the testator's object. The parent or grandparent may wish to provide that funds be set aside for infants and young people under the age of majority, in which case he will employ a trust in order that those funds shall be protected while the young people are incapacitated by minority.